Foot burns and diabetes: a retrospective study. Issue 1 (December 2015) - Lawrence, E.; Li, F.
Abstract Background Diabetes in conjunction with a foot burn can compound the challenges in wound healing; however, the impact of diabetes on outcomes of patients with foot burns has not been examined. Methods A retrospective notes audit was conducted at the Concord Hospital Burns Unit for patients with foot burns who were admitted from 1st January 2012 to 31st December 2013. Data were collected for 15 subjects with foot burns and diabetes and 18 subjects with foot burns and no diabetes as a control group. Subjects were matched for percentage total body surface area of burns. Results The mean inpatient and total lengths of stay for the diabetic group were 21.27 days and 64.80 days, which were significantly longer (P  = 0.090 andP  = 0.054) than the 9.61 days and 30.56 days in the control, based on a significance level of 0.10. The diabetic group was significantly older (P  = 0.001), at 56.60 years versus 39.44 years in the control. Significantly (P  = 0.033) more patients with diabetes were not working (n  = 12/15 or 80.00 % versusn  = 7/18 or 38.89 %) compared to the control. The diabetic group had higher rates of regrafting (n  = 3/15 or 20.00 % versusn  = 1/18 or 5.55 %) than the control and significantly (P  = 0.013) more amputations (n  = 5/15 or 33.33 % versusn  = 0 or 0.00 %) compared to the control. Fewer patients with diabetes were prescribed pressure garments (n  = 2/15 or 13.33 % versusn  = 9/18 or 50.00 %), which was significant (P  = 0.034). The increased age of patients in the diabetic group correlates with results from other studies. Healing time may be reflected by total length of stay, which was more than double for patients with diabetes, increasing demand and cost of inpatient and outpatient services. Conclusion This study highlights the importance of recognizing the potential for poorer outcomes for patients with diabetes and indicates the need for more burn prevention education and promotion in this 'at risk' patient group.